Fiqh Study of Bank Interest - Zahara Qifta isvara; Yunanta muhamammad hafiz (Jurnal Sahabat ISNU SU, 2025)
The study of Islamic jurisprudence (fiqh) on bank interest has given rise to diverse views among Islamic scholars. Most contemporary scholars consider bank interest to be usury (riba), which is forbidden in Islam, while others permit it, taking into consideration mutual consent and modern economic realities. This research uses a literature review method with a qualitative and comparative approach to classical and contemporary Islamic jurisprudence sources. The results of the study indicate that there are three main views: bank interest is forbidden because it is riba nasiah (usury of the Prophet); bank interest is permissible because it is considered a reward for services; and the subhat view, which tends to be cautious. These differences indicate that the law on bank interest is khilafiyah (disputed). Therefore, it is important for Muslims to understand the basis of the arguments behind each opinion and make choices based on peace of mind and the principles of Islamic sharia.